Up From the Tropics : Migratory Patterns of the Rose-Breasted Grosbeak - Morton, Hannah; Bell, Ashley; Ward, Sarah (My University, 2017)
The Rose-Breasted Grosbeak (RBGR) is a neotropical migrant that breeds in North America. We hypothesize that male RBGR will arrive earlier in spring than females to establish territories on their breeding grounds. We used bird banding data collected from banding stations in Ontario, Canada and Beaver Creek Reserve (BCR), Fall Creek, WI. Results from initial data sorting and analyses indicated that more males than females comprised the first date of arrival at both locations. In addition to analyzing historical data, as part of BIOL 490, we learned the methods of bird banding at BCR. Skills included catching birds in mist-nets, measuring wing chord lengths and weight, differentiating sex and age, helping with data collection and banding of the birds.
Color poster with text, maps, graphs, and images.
Keywords: Birds; Rose-breasted grosbeak; Migration; Posters